Regulation of Oocyte and Cumulus Cell Interactions by Intermedin/Adrenomedullin 2 - Chang, Chia Lin (American Society for Biochemistry and Molecular Biology, 2011)
Ovarian folliculogenesis has been studied as a model of hormonal regulation of development and differentiation, cell death, and cell-cell communication. In addition to gonadotropins from the pituitary and follicular paracrine factors, oocyte secreted factors have been shown to play critical roles in the regulation of follicular cell functions. Except for the well characterized BMP family proteins, including GDF9 and BMP15, oocytes are known to secrete oocyte secreted factors that are important for the regulation of cumulus cell survival and the maintenance of tertiary structure of cumulus cell-enclosed oocyte complexes (COCs). Based on genomic screening and studies of COCs cultured in vitro, we showed that intermedin (IMD)/adrenomedullin 2 (ADM2) is a novel oocyte-derived ligand important for the regulation of cell interactions in COCs that functions, in part, by suppressing cumulus cell apoptosis. Consistently, we showed that suppression of IMD/ADM2 signaling in growing rat ovaries in vivo leads to oocyte atresia and aberrant cell cycle progression in follicular cells. Together, our studies indicated that mammalian oocytes deploy a G protein-coupled receptor ligand to coordinate normal interactions of oocytes and cumulus cells and provided a better understanding of how the tertiary structure of a COC is maintained as follicles undergo exponential growth during the late stages of folliculogenesis.